Calculation of the activity inventory for the MNSR reactor using DRAGON4 code. (October 2018) - Al Zain, Jamal; El Hajjaji, O.; El Bardouni, T.
Abstract: A study on the fuel burnup and radioactive inventory of the Miniature Neutron Source Reactor (MNSR), after ten years of expected life of the reactor core, is conducted to validate the computer code DRAGON4 for the cluster geometry of the reactor. Excess reactivity of the reactor is calculated versus the fuel burnup time with different power levels 10, 15, 20, 25, and 30 kW. Furthermore, the concentrations and activities of the most important fission products, the actinide radionuclides accumulated, and the total radioactivity inventory of the MNSR core has been calculated using the DRAGON4 code and through comparison with the available results. A good agreement is observed between the present calculations of the DRAGON4 code, in addition to the previously published results of the GETERA and WIMSD4 codes. Highlights: Burnup calculations using the DRAGON Version4 deterministic code. Evaluation of burnup calculations versus the previous publications. Calculation of isotopic concentration considering neutron importance is performed. Study effect of burn up on neutron flux level. Good agreement was found between the present calculations for DRAGON-4 code and the previous published results for GETERA and WIMSD4 codes.